Talent Management Solusi dalam Meningkatkan Komitmen Organisasi - Dina Novita; Riyadi Nugroho; I Dewa Ketut Raka Ardiana (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
The company carrying out its operations is in a complex, diverse, dynamic, very competitive, and very volatile environment, and faces various potential problems that will arise. This requires the ability of talented individuals related to talent management practices who work with organizations to attract, develop, and retain talent. This research involved 198 employees in the city of Surabaya from various fields of work. Data collection was carried out using a questionnaire, while data analysis was carried out using Structural Equation Modeling (SEM). Based on the results of the study it can be concluded that salary satisfaction acts as a mediation for the relationship between talent management and organizational commitment, so talent management has a significant effect on organizational commitment through the mediation of salary satisfaction. perceptions of employee management talent produce a satisfactory relationship with salary, meaning that sensory policies are the main factor in shaping organizational mentality, but talent management strategies need to be developed with sensory systems to achieve greater financial effects in improving employee performance.